PREVENTION OF THE SYNDROME OF EMOTIONAL BURNING OUT AT TEACHERS OF PRESCHOOL EDUCATIONAL INSTITUTIONS - Л. Г. Богославец (Science and Innovation Center Publishing House, 2014)
Preschool educational institutions are unique since children for the first time get some skills of interaction and pedagogic influence. Thus basic tendencies of development and modernization of preschool education are connected with creation of favorable atmosphere and psychological climate in the team. Overcoming of negative consequences such as bad feeling, tiredness indicate emotional burnout of pedagogues of preschool educational institutions. Purpose. Prevention of a syndrome of emotional burning out at DOW’S teachers. Methodology researches and works on identification of the reasons, factors of emotional burning out of teachers of DOW. Results: stressovoustoychivost increase with installation of the favorable psychological atmosphere in staff of kindergarten. Practical implications: preschool education. Purchase on Elibrary.ru > Buy now